Introduction to LBXML Operator a Java API-based tool for XML insertion, modification, searching and removal. - Li, Bing
LBXML Operator is a Java API-based XML tool that supports insertion, modification, searching and removal on XML files. Of the many available XML parsers and XML tools, none provide APIs to complete the above functionalities when manipulation conditions become complex-they support only simple operations on XML.